Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$\sqrt{9-2\sqrt{23-6\sqrt{10+4\sqrt{3-2\sqrt{2}}}}}$

I have no idea how to unnest radicals, can anyone help?

share|cite|improve this question
    
What are you trying to do with this, simplify it or convert it to a decimal? – Jed Mar 7 at 1:23
    
Simplify; I know the answer which is $\sqrt{2} +1$ but no idea how to get it – Anonymous Mar 7 at 1:24
1  
In general, $a+b\sqrt{d}$ with $a,b,d$ integers might have a square root of the form $a'+b'\sqrt{d}$ only if $a^2-db^2$ is a square. That isn't a sufficient condition, but it is a good start. For example, you need $a+b\sqrt{d}>0$, and it doesn't help you find the square root. Finding the square root is often a trial by error with a little help from knowledge of "Pell-like equations." – Thomas Andrews Mar 7 at 1:42
up vote 6 down vote accepted

Here's a hint to give you the kind of idea involved:

The innermost term $3-2\sqrt2$ can be rewritten as $1^2-2\cdot1\cdot\sqrt 2+(-\sqrt{2})^2=(1-\sqrt 2)^2$ which cancels the square root it lies inside. Now simply and apply the same strategy of recognizing squares to keep canceling square roots until you are left with a simple expression.

Edit: How do we recognize these squares? The core idea lies in the "mixed term". Our goal is to make the term inside the current innermost radical look like either $(a+b)^2=a^2+b^2+2ab$ or $(a-b^2)=a^2+b^2-2ab$ which have middle terms $2ab$ or $-2ab$ respectively. So in our example, we had $-2\sqrt 2$, so you know that we're going to get something of the form $(a-b)^2$ with $$ab=\sqrt 2.$$ However, we need $$a^2+b^2=3.$$

At this point you one of the $a$ or $b$ as $\sqrt 2$ since it shows prominently in the $ab$ term. So $a^2+(\sqrt 2)^2=3$, so $a$ needs to be $1$. This checks out with $ab=\sqrt 2$. This last bit, you have to eyeball it a little bit.

share|cite|improve this answer
    
I see that, but are there any tricks to recognize these squares? – Anonymous Mar 7 at 1:38
1  
@Anonymous See my edit. Hope this helps! – Jake Mar 7 at 1:47

Suppose that the term $\sqrt{3-2\sqrt2}$ can be written as $\sqrt a + b$ for some $a,b\in\mathbb Z$. We can equate these expressions then square both sides: $$\sqrt{3-2\sqrt2} = \sqrt a + b\\ 3 - 2\sqrt2 = a+b^2 + 2b\sqrt a$$ and from here you can see that the solution is $(a,b) = (2,-1)$. This gives you a methodical approach that you can apply recursively.

share|cite|improve this answer

Observe that $$(\sqrt{2}-1)^2=2-2\sqrt{2}+1=3-2\sqrt{2}\qquad\implies\qquad\color{blue}{\sqrt{3-2\sqrt{2}}=\sqrt{2}-1}$$ Then, $$\color{blue}{\sqrt{10+4\sqrt{3-2\sqrt{2}}}}=\sqrt{10+4(\sqrt{2}-1)}=\sqrt{6+4\sqrt{2}}=\sqrt{4+4\sqrt{2}+2}=\color{blue}{\sqrt{(2+\sqrt{2})^2}}$$ So \begin{align} \sqrt{23-6\sqrt{10+4\sqrt{3-2\sqrt{2}}}}&=\sqrt{23-6(2+\sqrt{2})}\\ &=\sqrt{11-6\sqrt{2}}\\ &=\sqrt{9-6\sqrt{2}+2}\\ &=\sqrt{(3-\sqrt{2})^2}\\ &=3-\sqrt{2} \end{align} Finally \begin{align} \sqrt{9-2\sqrt{23-6\sqrt{10+4\sqrt{3-2\sqrt{2}}}}}&=\sqrt{9-2(3-\sqrt{2})}\\ &=\sqrt{3-2\sqrt{2}}\\ &=\sqrt{2}-1 \end{align}

share|cite|improve this answer

Work from the inside out.

Let $\sqrt{3 - 2\sqrt{2}} = \sqrt{a} - \sqrt{b}$, where $a$ and $b$ are rational numbers. Squaring both sides yields $$3 - 2\sqrt{2} = a + b - 2\sqrt{ab}$$ Then \begin{align*} a + b & = 3 \tag{1}\\ -2\sqrt{ab} & = -2\sqrt{2} \tag{2} \end{align*} Dividing equation by $-2$ yields $$\sqrt{ab} = \sqrt{2}$$ Squaring both sides of the equation yields $$ab = 2$$ Hence, $$b = \frac{2}{a}$$ Substituting for $b$ in equation 1 yields \begin{align*} a + \frac{2}{a} & = 3\\ a^2 + 2 & = 3a\\ a^2 - 3a + 2 & = 0\\ (a - 1)(a - 2) & = 0 \end{align*} Hence, $a = 1$ or $a = 2$. If $a = 1$, then $b = 2$. However, $\sqrt{1} - \sqrt{2} = 1 - \sqrt{2} < 0$, but $\sqrt{3 - 2\sqrt{2}} > 0$. Thus, $a = 2$ and $b = 1$. Hence, $$\sqrt{3 - 2\sqrt{2}} = \sqrt{2} - \sqrt{1} = \sqrt{2} - 1$$ Substituting $\sqrt{2} - 1$ for $\sqrt{3 - 2\sqrt{2}}$ yields $$\sqrt{10 + 4\sqrt{3 - 2\sqrt{2}}} = \sqrt{10 + 4(\sqrt{2} - 1)} = \sqrt{6 + 4\sqrt{2}}$$ Let $\sqrt{10 + 4\sqrt{2}} = \sqrt{c} + \sqrt{d}$, where $c$ and $d$ are rational numbers. Continue.

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.